Macro social theory, linguistic ethnography and interpreting research - Inghilleri, Moira (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article presents an outline of a sociological and linguistic-ethnographic perspective as applied to contexts of community interpreting. It describes a theoretical and methodological approach which, drawing on Toury ’s descriptivist theory of norms and Bourdieu ’s social reproduction theory, considers how relevant macro-social features impact on interpreting activity. This approach has as its aim to theorise configurations of the social in lo- cal interpreting contexts and to demonstrate how interpreters, as pivotal players in these contexts, are caught up in larger social configurations of power and control, both internal and external to their professional field of practice. It suggests that norms of interpreting activity and training can be linked to the wider social and political contexts of their occurrence. A descriptive language of interpreted events is developed which reflects participants’ embeddedness in social and political processes, and how this impacts on both actual and potential discursive moves within interpreted interactions. The sociological and linguistic-ethnographic perspective takes the view that what happens at the surface level of interactions is more often than not a micro drama through which a larger social and political reality is acted out in a refractedform.